Il viaggio di Verhaghen a Napoli. Immaginario europeo e dinamiche culturali a confronto - Moreno, Paola (Incontri. Rivista europea di studi italiani, 2012)
Verhaghen’s Voyage to Naples A European Vision versus Neapolitan Cultural Dynamics This short article sets out to describe the, at times strident, contrasts between actual Italian history, and the perception of such that informed the experience of eighteenth century Grand Tour visitors of the Italian peninsula. Central to this discussion is the Flemish painter Pieter Jozef Verhaghen’s Fall 1771 journey to Naples. A letter to his wife, included here − annotated and translated from the Flemish − sheds light on the distance spanned between the historical dynamics and local cultures, and the traveler’s expectations that, following a both physical and mental itinerary, proceed along a sort of circle that, in addition to exposing one to the other, still, in a most reassuring way, bring one back to oneself.